2018
DOI: 10.1016/j.celrep.2018.05.043
|View full text |Cite
|
Sign up to set email alerts
|

POGZ Is Required for Silencing Mouse Embryonic β-like Hemoglobin and Human Fetal Hemoglobin Expression

Abstract: Fetal globin genes are transcriptionally silenced during embryogenesis through hemoglobin switching. Strategies to derepress fetal globin expression in the adult could alleviate symptoms in sickle cell disease and β-thalassemia. We identified a zinc-finger protein, pogo transposable element with zinc-finger domain (POGZ), expressed in hematopoietic progenitor cells. Targeted deletion of Pogz in adult hematopoietic cells in vivo results in persistence of embryonic β-like globin expression without affecting eryt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
34
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 32 publications
(41 citation statements)
references
References 48 publications
6
34
1
Order By: Relevance
“…In particular, 78 out of 913 and 251 genes annotated to neurogenesis (GO: 0022008) in human and mouse, respectively, showed commonly differential expression between human and mouse (Supplementary Tables 4 and 5). Considering that POGZ represses gene transcription in hematopoietic cells 37,38 , we focused on the upregulated genes in NSCs derived from the patient and POGZ WT/Q1038R mice. We found that, among these differentially expressed genes involving neuronal development, a Notch ligand, Jagged canonical Notch ligand 2 (JAG2), was expressed approximately two-fold higher in NSCs derived from both the patient (fold change = 1.970) and POGZ WT/Q1038R mice (fold change = 2.175) compared to each corresponding control NSCs (Supplementary Tables 4 and 5).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, 78 out of 913 and 251 genes annotated to neurogenesis (GO: 0022008) in human and mouse, respectively, showed commonly differential expression between human and mouse (Supplementary Tables 4 and 5). Considering that POGZ represses gene transcription in hematopoietic cells 37,38 , we focused on the upregulated genes in NSCs derived from the patient and POGZ WT/Q1038R mice. We found that, among these differentially expressed genes involving neuronal development, a Notch ligand, Jagged canonical Notch ligand 2 (JAG2), was expressed approximately two-fold higher in NSCs derived from both the patient (fold change = 1.970) and POGZ WT/Q1038R mice (fold change = 2.175) compared to each corresponding control NSCs (Supplementary Tables 4 and 5).…”
Section: Resultsmentioning
confidence: 99%
“…The source data underlying figures e, g and i are provided as a Source Data file. transcription factor, heterochromatin protein 1 (HP1), and chromodomain helicase DNA-binding protein 4 (CHD4) [35][36][37] , which suggests that POGZ functions as a chromatin regulator; however, the role of POGZ in brain development and the biological significance of ASD-associated de novo POGZ mutations in the etiology of ASD are largely unknown.…”
mentioning
confidence: 99%
“…POGZ encodes a domesticated DNA transposase containing a cluster of multiple C 2 H 2 ‐type ZNF domains, a HTH domain, and a DDE domain (Bartholomeeusen et al, ; Nozawa et al, ). The expression pattern of POGZ in fetal brain tissues suggests that POGZ may play an essential role in early embryonic development (Gudmundsdottir et al, ; Stessman et al, ). Previous studies have shown that POGZ is involved in neuronal proliferation, neurite outgrowth, chromatin remodeling, and gene transcription regulation (De Rubeis et al, ; Gudmundsdottir et al, ; Hashimoto et al, ; Nozawa et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…The expression pattern of POGZ in fetal brain tissues suggests that POGZ may play an essential role in early embryonic development (Gudmundsdottir et al, ; Stessman et al, ). Previous studies have shown that POGZ is involved in neuronal proliferation, neurite outgrowth, chromatin remodeling, and gene transcription regulation (De Rubeis et al, ; Gudmundsdottir et al, ; Hashimoto et al, ; Nozawa et al, ). Genotype–phenotype correlation analysis has revealed that likely gene‐disrupting variants in POGZ define a potential ASD and ID syndrome (Stessman et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…We studied how Pogz dosage affect phenotypic outcome by generating heterozygote and homozygote knockout (KO) of Pogz. Since a complete KO of Pogz cause early embryonic lethality 25 , we crossed a conditional Pogz flox/flox (Pogz fl/fl ) mice with transgenic Nestin CRE (Nes Cre/+ ; Pogz fl/+ ) in order to produce heterozygous (Nes Cre/+ ; Pogz fl/+ ) and homozygous (Nes Cre/+ ; Pogz fl/fl ) mutation restricted to the brain (hereafter referred to as Pogz cKO +/and Pogz cKO -/-) ( Figure 1A).…”
Section: Brain-specific Deletion Of Pogz Does Not Results In Gross Defmentioning
confidence: 99%